2012
DOI: 10.1073/pnas.1109683109
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome regulates translation of mRNA in the cytosol

Abstract: An array of photoreceptors including cryptochromes, phototropin, and phytochromes regulates various light responses in plants. Among these photoreceptors, phytochromes perceive red and far-red light by switching between two interconvertible spectral forms (Pr and Pfr). The Pfr form promotes light responses partly by destabilizing negatively acting, phytochrome-interacting basic helix-loop-helix transcription factors (PIFs), thus modulating transcription in the nucleus. The Pfr form is also present in the cytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 52 publications
(60 reference statements)
3
68
0
Order By: Relevance
“…Recently, it has been shown that phytochrome also regulates the translation of protochlorophyllide reductase mRNA by directly interacting with the RNA-binding protein PENTA1 in the cytosol (13). Therefore, phytochrome has emerged as a direct regulator of various aspects of gene expression that interacts with different partners in different subcellular locations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that phytochrome also regulates the translation of protochlorophyllide reductase mRNA by directly interacting with the RNA-binding protein PENTA1 in the cytosol (13). Therefore, phytochrome has emerged as a direct regulator of various aspects of gene expression that interacts with different partners in different subcellular locations.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence suggests that light regulates not only transcription but also other aspects of gene expression, such as chromatin reorganization (12), translation (13,14), posttranslational modification (11,15), and pre-mRNA splicing (16)(17)(18). Pre-mRNA splicing is a posttranscriptional event that is carried out by a macromolecular complex called the spliceosome.…”
mentioning
confidence: 99%
“…In the nucleus, YHB acts similarly to the P fr form of phyB by binding PHY-TOCHROME INTERACTING FACTOR (PIF) basic Helix-Loop-Helix (bHLH) transcription factors and targeting them for degradation (for review, see Bae and Choi, 2008). More recently, signaling roles for P fr in the cytoplasm have been reported (Paik et al, 2012;Hughes, 2013). To evaluate the contribution of cytoplasmic P fr signaling into the circadian system, we introduced the G767R mutation into the YHB allele (YHB-G767R).…”
Section: Cytosolic Yhb Has Little Effect On Clock Gene Expression Ormentioning
confidence: 99%
“…Within the nucleus, the activated Pfr physically interacts with multiple proteins, including a small group of basic helix-loop-helix (bHLH) transcription factors called Phytochrome Interacting Factors (PIFs; PIF1 and PIF3 to PIF8) (Quail, 2000;Quail, 2002, 2005;Huq et al, 2004;Duek and Fankhauser, 2005;M. Chen et al, 2010;Galvão et al, 2012;Paik et al, 2012). PIFs constitutively accumulate in the nucleus in the dark and inhibit photomorphogenesis (Castillon et al, 2007;Henriques et al, 2009;Leivar and Quail, 2011).…”
Section: Introductionmentioning
confidence: 99%